Profile of Biology Students' Learning Styles at UIN KHAS Jember - Jannah, Annida Nur Izzatul; Maula, Naili ‘Atiqotul; Kurniasari, Putri Rizky; Citra, Wardha Kharisma (META: Journal of Science and Technological Education, 2022)
The Bioconservation course requires a great deal of contextual learning, enrichment, debate, and case studies in the field, hence it is taught in a blended learning format. If the teacher is aware of the student's learning styles, blended learning will be successful. As a result, knowing student learning styles is essential for the success of learning activities. A survey was utilized as the research technique, and the instrument was in the form of a closed angle. The information collected is quantitative. Percentages were used to examine the data. Respondents are State Islamic University KH. Achmad Shiddiq Jember class of 2020 Biology class 2 students enrolled in the Bioconservation course. The results of the study showed that students participating in the Bioconservation course had an auditive-visual learning style of 57.1%, followed by a visual, auditive learning style. Meanwhile, the visual-kinesthetic, auditive-kinesthetic and kinesthetic learning styles had the same percentage of 10.7%. Blended learning may be an option for accommodating different student learning styles. Journals are used by 85.7% of students as a source of learning, followed by books and internet references (learning websites), while 85.7% of students check for study references on their smartphones. The practice of students searching for reference materials on the internet through cellphones, as well as their learning style, has aided blended learning activities.